TRANSCRANIAL DOPPLER ASSESSMENT OF CEREBRAL BLOOD-FLOW VELOCITY IN TERM NEWBORNS - (:unkn) unknown (SPRINGER VERLAG, 1995)
Using the transcranial Doppler technique to assess postnatal changes in cerebral blood flow velocity, we studied the anterior cerebral artery, middle cerebral artery, and internal carotid artery of 31 healthy, term newborn infants. Normative values for the Ist, 3rd, and 5th days of life were determined. Cerebral blood flow velocity values in all three arteries examined correlated well with each other and we observed a statistically significant increase only in middle cerebral artery blood flow velocity between the 1st and 3rd, and 1st and 5th postnatal days. Thus, if we assume that flow velocities in various cerebral arteries undergo similar change, only one representative artery need be examined. The middle cerebral artery appears to be the vessel of choice. This choice simplifies the recording procedure, particularly in repeated examinations,
Keywords: CEREBRAL BLOOD FLOW VELOCITY; TERM INFANTS; DOPPLER ULTRASOUND; INFANTS